2021
DOI: 10.1002/rra.3804
|View full text |Cite
|
Sign up to set email alerts
|

Calcium concentrations in the lower Columbia River, USA, are generally sufficient to support invasive bivalve spread

Abstract: Dissolved calcium concentration [Ca 2+ ] is thought to be a major factor limiting the establishment and thus the spread of invasive bivalves such as zebra (Dreissena polymorpha) and quagga (Dreissena bugensis) mussels. We measured [Ca 2+ ] in 168 water samples collected along $100 river-km of the lower Columbia River, USA, between June 2018 and March 2020. We found [Ca 2+ ] to range from 13 to 18 mg L À1 during summer/fall and 5 to 22 mg L À1 during the winter/spring. Previous research indicates that [Ca 2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Other environmental variables, not measured by us in this study, are also likely to be important in regulating the abundance of C. fluminea , in particular calcium (and potentially other ions) and predation. For example, Bollens et al (2021) found that calcium concentrations necessary for supporting invasive bivalves like C. fluminea and Dreissena spp. are sufficient throughout the lower CR; however, the influence of organic or other inorganic nutrients have yet to be assessed in the CR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other environmental variables, not measured by us in this study, are also likely to be important in regulating the abundance of C. fluminea , in particular calcium (and potentially other ions) and predation. For example, Bollens et al (2021) found that calcium concentrations necessary for supporting invasive bivalves like C. fluminea and Dreissena spp. are sufficient throughout the lower CR; however, the influence of organic or other inorganic nutrients have yet to be assessed in the CR.…”
Section: Discussionmentioning
confidence: 99%
“…C. fluminea has since become well established in the CR (Henricksen & Bollens, 2022), reaching population densities of up to 722 individuals m −2 (McCabe et al, 1997). Despite these 80+ years of occurrence in the CR, as well as its known harmful effects in other invaded ecosystems, only a very limited body of scientific literature exists on the ecology of pelagic juveniles (Dexter et al, 2015;Dexter, Katz, Bollens, et al, 2020;Hassett et al, 2017) and benthic adult C. fluminea in the CR (Bollens et al, 2021;Henricksen & Bollens, 2022;McCabe et al, 1997;Rollwagen-Bollens et al, 2021), particularly regarding this species' habitat associations. variables, in its invaded range of North America, South America, and Europe, as well as its native range in Asia, Africa, and Australia, and to compare these findings to our results from the lower CR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation